Regulations ‘Under the Weather’: Legal Factors of Stability and Change for the Implementation of Natural Stormwater Management in Finland - Venuti, Francesco; Heinilä, Aleksi; Davids, Peter R. (Wiley, 2025)
The implementation of natural stormwater management (SWM), namely SWM carried out through nature-based solutions (NBS), is still problematic despite their benefits in climate change adaptation. Private landownership is commonly cited as the factor limiting extensive NBS. However, the Finnish model demonstrates that, regardless of whether the needed land is private or public, implementing actors face numerous legal challenges in efforts to carry out SWM using NBS. We study the Finnish SWM and land use planning frameworks to uncover the legal barriers to and drivers of NBS implementation as well as the interaction of the frameworks with the wider governance setting. By doing so, we highlight the need for a regulatory approach to NBS that will facilitate their uptake. We first explore how the Finnish legal framework regulates natural SWM. Secondly, we use the policy arrangement approach (PAA) and the framework on stability and change in flood risk management to combine the results of the legal analysis with the findings from a series of interviews with urban planners from several Finnish municipalities. This in turn enables us to visualise how the law interacts with the broader governance system to limit and shape the options for implementing natural SWM. The main factors of stability (namely, keeping the status quo) for NBS include the lack of regulations and unclear and fragmented SWM responsibilities. The main factors encouraging change include cities' acquisition or ownership of public land, an integrated governance approach to SWM, the Green Area Factor (GAF), pilot projects and stormwater working groups.